Medication-Related Burden and Medication Adherence Among Geriatric Patients in Kuwait: A Cross-Sectional Study - Abdelmoneim Awad; Anwar Alhadab; Abdullah Albassam (Frontiers Media S.A., 2020)
The evaluation of medicines burden from the patients' perspectives is a crucial endeavor to identify any barriers that may hinder achieving optimal health outcomes. Therefore, this study was designed, firstly to identify the prevalence of medication-related burden among geriatrics and factors influencing this burden. Secondly, to determine the prevalence of medication adherence and the correlation between the burden and adherence. A cross-sectional study was performed using Living with Medicines Questionnaire version-3 (LMQ-3) and Adherence to Refills and Medications Scale (ARMS) questionnaire. Four hundred and fifty patients attending primary healthcare centers were invited to participate, and 424 (94.2%) agreed. Data were collected via face-to-face structured interviews. The vast majority of respondents (97.4%; 95% CI: 95.3-98.6) perceived to suffer from minimum (35.4%) to moderate (62.0%) degrees of medicine burden. The median (IQR) LMQ overall score was 112 (21) indicating a moderate burden. LMQ-3 overall scores revealed a significant trend toward higher perceived burden among respondents aged ≥ 75 years, males, non-Kuwaitis, residents in Al-Farwaniyah and Al-Jahra governorates, using oral and nonoral formulations, paying prescription charges, and needing support with using medicines (p <0.05). Almost 55% (95% CI: 49.8-59.5) of respondents were nonadherent to their medications. The median (IQR) ARMS overall score was 20 (7.0) indicating low adherence to medications. There was a significant positive correlation between LMQ-3 and ARMS scores (p<0.001) showing that the higher the medications burden the lower the level of medication adherence. The key findings of this study underscore the need for multifaceted interventions that could be targeted at the identified problems to reduce medication burden and improve medication adherence.